Growth inhibition and apoptosis induction in two types of women cancer cell lines using laser ablated silver nanoparticles in polyvinylpyrrolidone solution - ALrawi, Nawfal N (Iraqi Journal of Cancer and Medical Genetics, 2017)
Silver nanoparticles (AgNPs) coated with polyvinylpyrrolidone (PVP) was prepared by pulsed laser ablation method inPVP solution, 1000 pluse was used with laser energy of 800 mJ/pulse. Formation of AgNPs-PVP was confirmed by UVvisiblespectrophotometer detecting surface plasmon resonance chang in the abilation solution. Concentration of AgNPs, sizedistribution, and surface charge of the ablated AgNPs in the produced solution was determined using atomic absorbtion spectroscopyand zeta potential analysis respectivly. Nanoparticles shape was determined using transmission electron microscopeimaging. Ability of the senthezied AgNPs to inhibit the growth of cancer cells was compared to that of normal fibroblast cellsusing two cancer cell lines (HeLa and SKOV-3) in different concentrations (0.78, 1.56, 3.125, 6.25, 12.5 and 25μg/ml). Theapoptosis events were also detected in both types of cancer cell lines using mitochondrial membrane permeability, nuclearmorphology, and genomic DNA fragmentation. The contribution of AgNPs to the levels of glutathione s-transferase was alsodetermined. According to the results, AgNPs size was 28.43nm with spherical shape and peak UV-Vis absorbance rangedbetween 402-410nm. Concentration of AgNPs in ablated solution was 50μg/ml and used as stock concentration in cell linesexperiments. Ablated silver nanoparticles was capable of inhibit the growth of both HeLa and SKOV-3 cancer cell lines indose and time dependent manner, whereas it was less inhibitory against normal fibroblast cells. All three apoptosis detectionmethod conducted indicated positive characteristics for apoptosis, while GSH levels did not varied significantly in both HeLaand SKOV-3 cells.Keywords: AgNPs, cancer cells, metal silver, Cytotoxicity, MTP, DNA fragmentation, GSH.